Предмет:
МатематикаАвтор:
аноним√(4 - 2x) + √(2 + x) = 2√2 ;
(√(4 - 2x) + √(2 + x))^2 = (2√2)^2 ;
4 - 2x + 2√(4 - 2x)(2 + x) + 2 + x = 4 * 2 ;
6 - x + 2√(8 + 4x - 4x - 2x^2) = 8;
2√(8 + 4x - 4x - 2x^2) = 8 - 6 + x;
(2√(8 - 2x^2))^2 = (2 + x)^2;
4(8 - 2x^2) = 4 + 4x + x^2;
32 - 8x^2 - 4 - 4x - x^2 = 0;
-9x^2 - 4x + 28 = 0;
9x^2 + 4x - 28 = 0;
За дискриминантом и формулами корней квадратного уравнения находим корни уравнения:
D = b^2 - 4ac = 4^2 – 4 * 9 * (-28) = 1024;
X1 = (- b + √D) / 2a = (-4 + √1024) / 2 * 9 = 28 / 18 = 14 / 9 = 1 5 / 9;
X2 = (- b - √D) / 2a = (-4 - √1024) / 2 * 9 = -36 / 18 = -2;
Ответ: 1 5 / 9; -2.
Автор:
scarlet1yh4Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть